PENGARUH KUALITAS LAYANAN DAN REPUTASI TERHADAP KEPERCAYAAN SERTA DAMPAKNYA PADA KOMITMEN PARTNER KERJA (Studi Pada Layanan Perbendaharaan Biro Keuangan Pemerintah Provinsi Jawa Tengah) - Rhameswari, Ayunda; Tjahjaningsih, Endang (Proceeding SENDI_U, 2016)
The purpose of this study to determine the effect of service quality and reputation of the trust of the partners workingin the service of Treasury Bureau of Finance Government of Central Java Province. To determine the effect ofservice quality, reputation and confidence in the commitment to work on the service partner of Treasury Bureau ofFinance Government of Central Java Province. To find out if the trust partner at mediating influence of the qualityof service and commitment to partner reputation to work at the service of Treasury Bureau of Finance Governmentof Central Java Province. The population in this study is that all agencies (SKPD) in Central Java ProvincialGovernment is known to number as many as 50 SKPD and 10 collaborators from outside (private). With a samplingtechnique using census sampling is a way of selecting respondents by taking the overall population is, therefore, asample of 60 respondents. Methods of data analysis using descriptive analysis, test instrument, namely the validityand reliability, test models and hypothesis testing. Based analyst who conducted the study concluded that the qualityof service partially (individual) positive and significant impact on the trust. Reputation partially (individual)positive and significant impact on the trust.Quality of service partially (individual) positive and significant effect oncommitment.Reputation partially (individual) positive and significant effect on commitment.Belief in partial(individual) positive and significant effect on commitment.Trust does not mediate the effect of quality of service andreputation for commitment.Keyword : service quality, reputation, trust, and commitment